Plantas tintóreas utilizadas en el teñido de textiles artesanales en el Perú - López Chacón, Santos Octavio (2015)
The aim of this review is to know and analyze the different dye plants which are used for dyeing textile craft. To do an exploratory methodological approach was used to collect information from different literature sources, the most important information regarding selected and analysis was arrived at by comparing the research found. Proper organization of existing species on their records dyeing characteristics making use categories for the same species in addition to a list providing information on the useful parts for pigments and some aspects of extraction of each species were executed was conducted at the end . 53 species of dye plants most popular with 41 families are reported, all with the ability to produce pigments of different colors highlighting the yellow, blue, red, and black which are used in the dyeing of textile craft.